Knowledge, Attitude and Practices About Travel Vaccine Among Medical Students and Doctors in A Tertiary Health Institution, Indore, Madhya Pradesh, India - Upadhyay, Ritesh; Tandia, Deepika; Thakur, Apurv B; Wavare, Rajshekhar R; Deshpande, Ajit (National Journal of Community Medicine, 2016)
Background: Travelers play a significant role in the spread of infectious diseases across international borders, through their travel patterns and behaviors. This study was conducted to assess the Knowledge, Attitude and Practices regarding travel vaccine among medical students and doctor. Materials and Methods: A cross-sectional study was conducted at SAMC & PGI, Indore from July to September 2015 using quantitative method of data collection among 114 medical student and doctors. Result: The mean age of the respondents was 27.85 years with 68 (59.65%) males and 46 (40.35%) female respondents. 21(18.42 %) participants are married and 93 (81.58 %) are single. 88.60 % of the respondents were aware of the concept of travel vaccines while 88.33 % of the respondents could give correct definition of travel vaccine. Knowledge regarding travel vaccine was found to have improved the uptake of travel vaccine (P = 0.04). Conclusion: The study shows that as the knowledge improves the uptake of travel vaccine increases significantly.